160k views
0 votes
Solve by any method (graphing, substitution or linear combination)

y = x - 8
2x + 3y = 1

a) (2, -6)

b) (5, -3)

c) (4, -4)

d) (0, -8)

I figured it out. The answer is (5, -3)

1 Answer

5 votes

Answer:

b) (5, -3)

Explanation:

The given equations are;


y=x-8...(1)


2x+3y=1...(2)

I prefer using substitution because of the first equation.

Put equation (1) into equation (2) to obtain;


2x+3(x-8)=1

We expand the parenthesis to obtain;


2x+3x-24=1

Group similar terms to get;


2x+3x=1+24

Simplify


5x=25

Divide through by 5;


x=(25)/(5)


\Rightarrow x=5

Put
x=5 into equation (1) to get;


y=5-8


\Rightarrow y=-3

The solution is (5,-3).

The correct answer is B

User Shovalt
by
5.4k points